An uncommon elbow injury in a baseball player - Mehallo, C. J. (The Physician and Sportsmedicine, 2004)
21-year-old minor league catcher who fell and landed on his elbow while running to first base had swelling and decreased range of motion, yet no deformity or neurovascular compromise that would have suggested dislocation. Radiographs provided the main diagnosic clue and guided the course of treatment.